Tenjing Sherpa: capstone - Sherpa, Tenjing, artist (Colorado State University. Libraries, 2024)
The artist's statement: My design work focuses on creating visually attractive graphics that attracts viewers' sight. I mainly focus on research and the repetition of creating multiple ideas until I break them down individually. Though I have many resources for various Adobe Suite applications, my sketchbook is the primary source of creativity. I can physically draw many different concepts and have ideas saved on multiple pages. My design purpose is to create minimalistic imagery that helps guide the viewers' eyes into understanding information.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design